Survey of the Ethiopian linyphiid spider fauna. II. Subfamily Micronetinae Hull, 1920 (Arachnida: Araneae: Linyphiidae) - Andrei V. Tanasevitch (European Journal of Taxonomy)
Seven species of the subfamily Micronetinae Hull, 1920 have been discovered in the Oromia Region, Ethiopia, five of which being described as new: Canariphantes trichofer sp. nov. (♂, ♀), Lepthyphantes bryocola sp. nov. (♀), L. chilalo sp. nov. (♂, ♀), L. legatus sp. nov. (♂, ♀), and Metaleptyphantes subclavator sp. nov. (♂, ♀). The male of L. bituberculatus Bosmans, 1978 is redescribed and illustrated, its corresponding female here being described for the first time. The genus Metaleptyphantes Locket, 1968 is transferred from the subfamily Ipainae Saaristo, 2007 to Micronetinae, based mainly on the micronetine-like structure of the embolic division, despite its capsula-on-solenoid-type of the epigyne. A diagnosis of the tropicalis species-group of the genus Lepthyphantes Menge, 1866 is refined, its species list is replenished. Agyneta prosectes (Locket, 1968) is recorded from Ethiopia for the first time. The taxonomical status of the subfamily Micronetinae is discussed.